Heat- and drought-resistance of some representatives of the genus Rhododendron L. - N. Nuzhyna; V. Kondratiuk-Stoyan (Vìsnik: Kiïvsʹkij Nacìonalʹnij Unìversitet Imenì Tarasa Ševčenka. Bìologìâ, 2017)
Data about changing the content of photosynthetic pigments in leaves of plants Rhododendron makinoi, R. degronianum, R. сallimorphum and R. brachycarpum after exposure to high temperatures are presented. Established degree of drought resistance of these plants. The most drought- and heat-resistant species are plants of Japanese origin.